Cross‐listings and dividend size and stability: evidence from China. (11th December 2019) - Cheng, Zijian; Cullinan, Charles P.; Liu, Zhangxin (Frank); Zhang, Junrui
Abstract: We investigate the relationship between cross‐listings and dividend policy. We find that Chinese cross‐listed firms have lower and more stable dividends than their non‐cross‐listed peers, and that dividends become more stable the longer a company has been cross‐listed. We also find the strength of the cross‐listing/dividend policy relationship varies based on the market where the shares are cross‐listed. The strength of the relationship varies from B‐shares (least strong) to Hong Kong shares (stronger) to American Depository Receipts (strongest). Our results indicate cross‐listings may influence both dividend size and stability, and that this influence can vary by the type of cross‐listing.